A Photovoice Study: The life experiences of middle‐aged adults with intellectual disabilities in Korea. Issue 3 (8th March 2021) - Kim, Min Ah; Yi, Jaehee; Bradbury, Laura; Han, Ki‐myung; Yang, Jieun; Lee, Jinseung
Abstract: Background: As adults with intellectual disabilities approach older adulthood, they face unique physical and psychosocial challenges. This study explored the lived experiences of middle‐aged adults with intellectual disabilities living in their community. Method: Six sessions of Photovoice were conducted with a purposeful sample of six middle‐aged adults with intellectual disabilities in South Korea. Participants were involved with the theme selection, taking photographs related to the themes, group discussion of photo stories and sharing Photovoice outcomes. Results: Thematic analysis yielded 11 subthemes under the five major themes selected by the participants: health, free time, time in the centre, family and my future in old age. Conclusions: The study findings showed complex issues middle‐aged adults with intellectual disabilities may face in later life, including bereavement and healthy lifestyle concerns. It is important to create a space for meaningful social support and social interactions without stigma.